Kajian taksonomi penyakit bulai pada tanaman jagung dan pengendaliannya - wahyudi, wahyudi; Selviani, Zakiah; Wati, Tri Agus Setiya; Sari, Ni Nengah Yulyani Purnami; Jayanti, Watini Hefri; Dirmawati, Suskandini Ratih; Aeny, Titik Nur; Suharjo, Radix (Jurnal Proteksi Agrikultura, 2025)
Downy mildew disease in maize plants (Zea mays) caused by the pathogen Peronosclerospora maydis is a serious threat to maize production in Indonesia, which is one of the main food commodities. The disease can cause significant crop yield losses, so a deep understanding of the taxonomy, epidemiology, and control strategies of the disease is important. This study aims to identify the taxonomy of downy mildew, analyze environmental factors that affect the progression of the disease, and evaluate various effective control methods, both chemically and biologically. Downy mildew control is carried out through an integrated approach which includes the use of resistant corn variations, the application of crop rotation systems, environmental sanitation, and seed treatment with metalaxic fungicides. In addition, the use of biocontrol agents such as Trichoderma spp. and Pseudomonas fluorescens showed great potential in reducing infections by up to 75% and significantly improving crop yields. This study also highlights the importance of the development and application of plant-based fungicides derived from natural ingredients such as turmeric, garlic, and soursop leaves, which have antimicrobial properties. Although the use of biocontrol agents has been implemented in some areas, the adoption of this technology is still limited, so more research is needed to explore the potential of other biocontrol agents. These findings are expected to contribute to the development of sustainable downy mildew control strategies, increase corn productivity, and support national food security.